The use of magnetic resonance in myocardial ischaemia - De Filippo, M.; Sudberry, J.J.; Borgia, et al., D. (Acta Biomedica Atenei Parmensis, 2005)
Despite the efforts that have been made at an international level to identify and control cardiovascular risk factors, cardiopathies and, in particular, coronary artery disease (CAD), remain the principal cause of death in Europe and the United States. These data confirm the importance and necessity of noninvasive, reliable diagnostic imaging of early CAD. Coronary angiography is still the hinge, around which all instrumental and laboratory investigations turn, for cardiac ischaemia today. Indeed, it still holds the role of “gold standard” for the study of the coronary arterial lumina, particularly the smaller vessels due to their complex spatial geometry and because of cardiac motion. At present, with the exception of the study of the coronary arterial lumen, MR is a non-invasive examination, already capable of supplying precise global and regional function, the evaluation of the intra-cardiac flow, myocardial perfusion and the overall viability of the heart.